Problem Solving: Economic Learning Strategies - Wahyu Muh. Syata; Abdullah Igo B.D; Bellona Mardhatillah Sabillah (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2023)
The ability to control learning is one that teachers must possess. One of the techniques a teacher should use in the educational process is problem solving. With the use of creative and innovative learning strategies, this article intends to help teachers, in particular, comprehend how to build information in a methodical manner. In order to give a thorough knowledge and rich perspective on learning processes through problem solving, this method of study uses a descriptive qualitative method to justify the analysis of the literature. According to the findings of this research, problem solving is necessary to help pupils develop their metacognitive and critical thinking abilities. Students are able to build their own potential via problem solving, which shifts their attention away from results alone.. Students' decision-making, critical thinking, and generation of creative and innovative concepts are stimulated by difficulties, which are provided to them. The growth of decision-making, critical thinking, and creative thinking that is innovative leads learners to reflect on their decision-making processes in daily life. Improved teachers' skills and abilities, can generate creative and innovative ideas so that they can identify and analyze the problems faced by the students. In order to identify and analyze problems, a teacher needs to implement strategies in solving them. Problem solving provides solutions in the learning process so that learning is more attractive, teachers in generalization or transfer of learning to pupils. Problem solving enables graduate students to think critically and solve problems in their personal, social and professional lives in order to enter the world of their future business.